Managerial Overconfidence and Market Feedback Effects - Banerjee, Suman; Huang, Shiyang; Nanda, Vikram; Xiao, Steven Chong (Management Science, 2023)
We show that managerial learning from stock prices can lead to feedback loop vulnerability: corrective actions based on perceived negative market signals reduce the sensitivity of asset payoffs to stock market information. Less sensitivity discourages liquidity provision and increases the price impact of liquidity shocks. Interestingly, overconfident managers who disregard stock price information may be less vulnerable to the adverse price impact of nonfundamental liquidity shocks. Our empirical evidence strongly supports the model’s underlying premises and predictions: First, investment decisions of overconfident CEOs are significantly less responsive to stock price fluctuations. Second, the price impact of liquidity shocks, for example, mutual fund fire sales, is substantially smaller for firms with overconfident CEOs. This paper was accepted by Gustavo Manso, finance. Funding: S. Huang gratefully acknowledges the financial support from the Hong Kong General Research Fund [GRF Project Code 17503317]. Supplemental Material: Data and the internet appendix are available at https://doi.org/10.1287/mnsc.2022.4625 .